Ecosystem Impacts of Artificial Snowmaking at Arizona Snowbowl - Niraula, Bikram Kumar (Arizona-Nevada Academy of Science, 2006)
From the Proceedings of the 2006 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - April 8, 2006, University of Arizona, Tucson